Treatment of Left Anterior Descending Artery Aneurysm - Mirsad Kacila; Marco L.S. Matteucci; Stefano Bevilacqua; Nermir Granov; Mattia Glauber (Biomolecules & Biomedicine, 2008)
Coronary artery aneurysms (CAAs) are rare and their management is controversial. Their incidence varies from 1,5% to 5% of the coronary angiographies, with predilection of the right coronary artery. Unruptured coronary aneurysms are often silent and may remain undiagnosed. The etiology can be either congenital or acquired. We describe a case of a left anterior descending artery (LAD) aneurysm treated with an off-pump surgical revascularization with a LIMA to LAD without exclusion or ligature of the aneurysm.